2022
DOI: 10.1038/s41598-022-07703-5
|View full text |Cite
|
Sign up to set email alerts
|

Shared barriers and facilitators to enrollment of adolescents and young adults on cancer clinical trials

Abstract: Adolescent and young adult (AYA) enrollment in cancer clinical trials (CCT) is suboptimal. Few studies have explored site level barriers and facilitators to AYA enrollment on CCTs and the efficacy of interventions to enhance enrollment. A cross sectional survey was developed by the COG AYA Oncology Discipline Committee Responsible Investigator (RI) Network to identify perceived barriers and facilitators to enrollment, as well as opportunities to improve enrollment. Associations of barriers and facilitators to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The AYA RI Network now includes local site AYA champions, including pediatric and medical oncology providers, from more than 120 institutions working together to boost local AYA clinical trial enrollment. The network has identified additional accrual barriers through regular webinars and workshops, has developed a Frequently Asked Questions document addressing common questions and misconceptions on how to cross‐enroll AYAs onto NCTN trials, and developed novel strategies leveraging communication technology to further improve enrollment 36,37 …”
Section: Strategic Approach: the Path Forwardmentioning
confidence: 99%
See 1 more Smart Citation
“…The AYA RI Network now includes local site AYA champions, including pediatric and medical oncology providers, from more than 120 institutions working together to boost local AYA clinical trial enrollment. The network has identified additional accrual barriers through regular webinars and workshops, has developed a Frequently Asked Questions document addressing common questions and misconceptions on how to cross‐enroll AYAs onto NCTN trials, and developed novel strategies leveraging communication technology to further improve enrollment 36,37 …”
Section: Strategic Approach: the Path Forwardmentioning
confidence: 99%
“…The network has identified additional accrual barriers through regular webinars and workshops, has developed a Frequently Asked Questions document addressing common questions and misconceptions on how to cross-enroll AYAs onto NCTN trials, and developed novel strategies leveraging communication technology to further improve enrollment. 36,37 The COG AYA RI Network will continue to foster site-level participation in newly developed NCTN and NCORP AYA trials via regular webinars for presentations by study chairs. Newer approaches to improve accrual are under investigation, including a multisite quality improvement initiative known as ATAQI (AYA Trial Access Quality Initiative).…”
Section: Foster Aya Clinical Trial Enrollmentmentioning
confidence: 99%
“…The development of cross-network AYA CCTs from concept inception was an important step taken by National Cancer Institute National Clinical Trial's Network (NCTN) to improve AYA accrual and there is currently a large, and growing, portfolio of available AYA therapeutic trials. There have been challenges to cross-enrolling AYAs on cross-network CCTs due to limited knowledge of the process and differences in treatment approaches between pediatric and medical oncologists, though many of these barriers are currently being addressed by The Children's Oncology Group AYA Responsible Investigator Network [41 ▪ ,42]. The network has developed cross-enrollment frequently asked questions (FAQs), empowered site champions to increase local AYA enrollment, and led a series of webinars on opportunities to overcome barriers to enrollment.…”
Section: Clinical Trial Enrollmentmentioning
confidence: 99%
“…[19][20][21][22] For example, retrospective review of cooperative group clinical trial data revealed that AYAs of the same age with acute lymphoblastic leukemia (ALL) have superior survival when treated on pediatric rather than adult trials (event-free survival: 34%-41% v 63%-79%, P , .0001). [23][24][25] Theoretical frameworks of barriers to clinical trial enrollment 26 and use of a novel style of therapy (pediatric v adult) 27 cite the key role of physician and staff collaboration across medical and pediatric oncology.…”
Section: Introductionmentioning
confidence: 99%